The Mediation Effect of Social Media Fomo on Islamic Guidance and Counseling and Juvenile Delinquency: A Study at Universitas Muhammadiyah Surakarta - Faqih Nur Muhlis; Hafidz Hafidz (Kamaya: Jurnal Ilmu Agama, 2026)
The rapid development of social media has triggered the Fear of Missing Out (FOMO) phenomenon among adolescents, which is often linked to various forms of juvenile delinquency. This study aims to analyze the influence of social media and FOMO on juvenile delinquency and evaluate the role of Islamic Guidance and Counseling (BKI) in addressing these issues. This research uses an associative quantitative approach conducted at Universitas Muhammadiyah Surakarta. Data were collected from 123 active social media users aged 17-23 using purposive sampling and analyzed through Path Analysis using Stata software. The results demonstrate that juvenile delinquency has a strong positive contribution to FOMO (β = 0.866), which in turn significantly increases the perceived necessity of BKI (β = 0.707). Interestingly, juvenile delinquency does not exert a direct influence on the demand for BKI (p = 0.646). The study concludes that FOMO acts as a perfect mediator (full mediation) between juvenile delinquency and BKI. Theoretically, this underscores that BKI interventions are recognized as vital not merely due to overt behavioral deviations, but precisely when such deviations sublimate into psychosocial anxiety or FOMO. Hence, BKI offers a critical spiritual-cognitive framework for addressing internal emotional distress rather than just external misconduct. Future research should explore external variables such as parenting styles and digital literacy to enrich the model.